Increased Awakenings From Non-rapid Eye Movement Sleep Explain Differences in Dream Recall Frequency in Healthy Individuals - van Wyk, Mariza; Solms, Mark; Lipinska, Gosia (Frontiers in Human Neuroscience, 2019)
Background: Dreaming is a universal experience, yet there is considerable inter-individual variability in dream recall frequency (DRF). One dominant model, the ‘arousal-retrieval’ model, posits that intra-sleep wakefulness is required for dream traces to be encoded into long-term storage, essentially proposing that a better memory for dreams underlie increased DRF. A recent study utilizing polysomnography combined with an event-related potentials paradigm, provides support for this model by demonstrating increased intra-sleep wakefulness in a healthy population by comparing high frequency recallers (HFRs) and low frequency recallers (LFRs). Another study by the same group demonstrated increased regional cerebral blood flow in regions associated with dream production, supporting the premise that HFRs also may produce more dreams. Hypotheses: We investigated the profile of nocturnal awakenings and dream production in healthy HFRs and LFRs. Hypothesis (1a): HFRs will spend significantly more time awake after sleep onset; (1b): HFRs will experience significantly more awakenings across the night, and from rapid eye movement (REM) sleep in particular; (2) HFRs will have significantly higher rates of dream production across the night as measured by REM density. Methods: We studied two groups of healthy adults: HFRs (n = 19) and LFRs (n = 17) who underwent polysomnographic recordings on two non-consecutive nights. Results: Hypothesis (1a) was confirmed: HFRs spent significantly more time awake after sleep onset. Hypothesis (1b) was partially confirmed: HFRs experienced significantly more awakenings across the night; however, awakenings from REM sleep were comparable. Interestingly, HFRs had significantly more awakenings, as well as a higher number of longer awakenings, from non-rapid eye movement (NREM) stage 2 sleep. Hypothesis (2) was not confirmed: There was no significant difference in rates of REM density between groups. Conclusion: This is the first study to provide evidence that awakenings from NREM 2 sleep might underlie increased DRF in HFRs. This finding coupled with null findings relating to REM sleep variables, support the premise that inter-individual variability in DRF cannot be ascribed to differences in REM sleep parameters in healthy individuals. Instead, the data indicates that awakenings from NREM sleep is of particular importance in relation to DRF in a healthy population.